Energy performance of PV integrated office buildings with fan-assisted double skin façades under tropical climates. Issue 13 (21st October 2019) - Barbosa, Sabrina; Carlo, Joyce; Ip, Kenneth
ABSTRACT: Building upon the knowledge accumulated from a comprehensive research program on double skin façades (DSFs), this study explores two design enhancements for buildings in tropical climates. Thermal and energetic benefits of the inclusion of mechanical ventilation within the DSF cavity and electricity generation from the PV systems have been determined across a wide spectrum of Brazilian climates. Using computational simulations, DSF models with two fan configurations, placed solely at the top of the DSF and distributed along the height of the cavity, are evaluated. Annual distribution of thermal comfort acceptance and impact on energy demands from HVAC systems and contribution from the PV systems is analyzed. Results demonstrated wide variations of energy performance in relation to the climatic conditions. The 'Cool' climate zone presented most significant benefits from the proposed design enhancements resulting in electricity surplus. On the other hand, electricity generated from PV in the moderate climate zone can only cover about 30% of the HVAC energy consumption, whereas energy savings in the 'hot' zone are the lowest with only 15% of electricity contributed from the PV systems. The results of this paper contribute to the early stage of design when considering the adoption of DSF in tropical climates.